High-strength low-thermal-conductivity SiC-TiO2 nanofiber aerogel and preparation method thereof

By growing the TiO2 nanorod structure on the surface of SiC nanofibers and using Si sol adhesive to form bonding points, a high-strength, low-thermal conductivity SiC-TiO2 nanofiber aerogel was constructed, which solved the shortcomings of ceramic aerogels in terms of structural stability, shear strength and high-temperature thermal conductivity, and achieved excellent mechanical properties and low thermal conductivity.

CN119735450APending Publication Date: 2025-04-01YANGTZE DELTA REGION INST (QUZHOU) UNIV OF ELECTRONIC SCI & TECH OF CHINA
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411923106.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing ceramic aerogels have shortcomings in structural stability, shear strength, and high-temperature thermal conductivity, making it difficult to maintain performance in extreme high-temperature environments.

Method used

Multi-stage layered SiC-TiO2 nanofiber aerogel is constructed by growing the TiO2 nanorod structure in situ on the surface of SiC nanofibers and forming a stable bonding point using Si sol adhesive during high-temperature calcination.

Benefits of technology

It significantly improves the mechanical stability and high-temperature thermal insulation properties of the aerogel, enhances compressive strength and shear resistance, and reduces the thermal conductivity at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735450A_ABST
    Figure CN119735450A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nano porous materials, discloses a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel and a preparation method thereof, and aims to solve the problems of insufficient structural stability, shear strength and high-temperature thermal conductivity of traditional ceramic aerogel. TiO2 nanorods are introduced onto a SiC nanofiber membrane by adopting an in-situ growth technology, and the high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel is prepared. And constructing the SiC nano composite fiber membrane into the layered porous ceramic nanofiber aerogel with a multilevel structure by combining a layer-by-layer stacking method with a directional freezing casting technology. TiO2 nanorods growing on the surface of the SiC fiber in situ serve as a secondary structure, so that the overall mechanical performance of the material is enhanced; the TiO2 nanorods have specific high infrared light reflection and scattering capabilities, so that the transmittance of the aerogel material to radiation is reduced, and the thermal radiation conduction in a high-temperature environment is effectively reduced. In addition, a silica sol binder is introduced between layers of the aerogel multilevel structure, stable bonding points are formed between fibers after calcination, and the mechanical stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanoporous materials, and in particular to a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel and a preparation method thereof. Background Art

[0002] Porous ceramic materials have the characteristics of high melting point and good chemical stability, and can maintain their structural stability and thermal insulation properties in high temperature environments. However, the three-dimensional network skeleton structure of traditional ceramic aerogels is composed of a pearl necklace-like structure formed by the aggregation of nanoparticles. Due to the limited binding force between nanoparticles, the material is brittle and prone to structural collapse when subjected to external forces. At the same time, when subjected to thermal shock, the sintering of particles and the collapse of the pore structure cause the material to shrink significantly in volume, which seriously limits the practical application of aerogels as thermal insulation materials in extremely high temperature environments.

[0003] One-dimensional ceramic nanofibers have a high aspect ratio and good flexibility, and show great application prospects in many fields. Ceramic nanofiber aerogel is a new type of ceramic material composed of continuous nanofibers, combining the advantages of ceramic materials and nanofibers. In the preparation process of elastic ceramic nanofiber aerogel materials, it is usually necessary to break the nanofiber membrane made by electrospinning into dispersed short fibers, which reduces the contact area between fibers and reduces the stability of the structure, making it difficult for the aerogel to resist thermal shock under extreme conditions. For example, An et al. (Ceramics International 2019, 45, 22793-22801) used a fiber freeze casting method to reconstruct a two-dimensional electrospun SiC fiber membrane into a three-dimensional porous SiC fiber aerogel, and in situ grew a SiC whisker structure inside the fiber skeleton by adjusting the heat treatment temperature. The aerogel exhibits a low density (0.039-0.041g cm -3), low thermal conductivity (0.025-0.031W / (m·K)) and 40% elastic deformation capacity, but its maximum compressive strength is still limited. Zhang et al. (ACS Nano 2023, 17, 21813-21821) used SiC nanofibers as building blocks and used AlBSi sol to construct bonding points between fibers. After directional freeze drying and heat treatment, an elastic SiC nanofiber aerogel was obtained, which can withstand 55% elastic strain, but its maximum compressive strength is less than 2kPa. Therefore, the researchers envisioned a way to construct an aerogel with a layered porous structure by stacking fiber membranes layer by layer, which is conducive to enhancing its overall compressive strength. For example, Zhang et al. (ACS Nano 2020, 14, 15616-15625) used ZrO2-Al2O3 fiber membrane as a building unit and combined it with aluminum dihydrogen phosphate high-temperature binder to obtain a superelastic layered multi-arch structure ZrO2-Al2O3 nanofiber aerogel, which can withstand up to 90% elastic strain and quickly recover to its original state, with a maximum compressive strength of 1100kPa. At the same time, ZrO2-Al2O3 nanofiber aerogel has a high porosity and low density, and its room temperature thermal conductivity is as low as 0.0322W / (m·K), indicating that it not only has super mechanical strength and excellent elasticity, but also has excellent thermal insulation properties. However, although the aerogel exhibits excellent compression resilience, the lack of strong interfacial bonding between layers leads to its poor shear resistance, with a maximum shear stress of only 4kPa, which makes it difficult to resist stress shocks and shear damage generated during complex processing.

[0004] In addition, as a thermal insulation material, the thermal insulation ability of ceramic aerogel at high temperature has a vital impact on the expansion of its application field. However, the radiation thermal conductivity Krad usually increases proportionally with the cube of the temperature. In a high temperature environment, radiation heat transfer dominates, resulting in the thermal conductivity of the aerogel still being very high in a high temperature environment. At present, in order to reduce the high-temperature thermal conductivity of aerogel, researchers usually add a class of infrared sunscreen materials into the aerogel, such as TiO2, carbon black and SiC particles. For example, Huang et al. (Ceramics International 50 (2024) 47892-47901) designed a PAN nanofiber loaded with TiO2 particles as a sunscreen material, which gave SiTiOC / PS / TiO2 hybrid aerogel excellent high-temperature thermal conductivity. Its thermal conductivity was only 0.0623W / (m·K) in an environment with a temperature of up to 600°C. Therefore, from the perspective of the practical application of materials, it is of great significance to develop a ceramic aerogel with comprehensive properties such as excellent mechanical properties and low thermal conductivity. Summary of the invention

[0005] The present invention aims at the problems that the existing ceramic aerogels are insufficient in terms of structural stability, shear strength and high-temperature thermal conductivity, and provides a high-strength and low-thermal conductivity SiC-TiO2 nanofiber aerogel and a preparation method thereof through microstructure design. The aerogel material not only has the characteristics of high porosity, ultra-lightness and excellent thermal stability of traditional ceramic aerogels, but also the TiO2 nanorod secondary structure constructed on the surface of SiC nanofibers effectively improves the overall mechanical stability and high-temperature thermal insulation performance of the aerogel. In addition, the introduced Si sol binder will form a Si-O-Si cross-linked network at the fiber nodes during the high-temperature calcination process of the aerogel, and evenly adhere to the fiber surface to form welding points, thereby forming a strong fiber skeleton, further avoiding inter-fiber slippage and structural collapse under the action of external stress.

[0006] To this end, the present invention provides the following technical solutions:

[0007] The invention provides a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel. The ceramic fiber aerogel consists of a multi-level layered SiC nanofiber membrane and a silica sol binder, wherein the silica sol binder with TiO2 nanorod structure in situ grown on the surface of the multi-level SiC fiber membrane forms a stable bonding point between the fibers.

[0008] The present invention also provides a method for preparing a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel, which is characterized by comprising the following steps:

[0009] Step (1) polycarbosilane, tetrahydrofuran, ethanol and a spinning aid are mixed and stirred in a mass ratio of 2-3.5:10-18:2-8:0.5-0.8 to form a spinning solution, and then the spinning solution is subjected to an electrospinning process to form a precursor nanofiber membrane, and the fiber membrane is heat-treated to obtain a SiC nanofiber membrane;

[0010] Step (2) adding tetrabutyl titanate to an acidic aqueous solution and mixing and stirring to obtain a reaction solution A, immersing the SiC nanofiber membrane in the reaction solution A for hydrothermal reaction, washing, drying and calcining to obtain a product A, wherein the volume ratio of tetrabutyl titanate: acid source: water is 1:8-12:22-30;

[0011] Step (3) mixing melamine, nitric acid and hydrogen peroxide in a molar ratio of 0.01-0.05:0.5-0.8:50-60 to prepare a reaction solution B, soaking the product A in step (2) in the reaction solution B, and then repeatedly filtering and soaking, washing, drying and calcining to finally obtain a SiC nanofiber membrane with a uniform TiO2 nanorod layer on the fiber surface;

[0012] Step (4) prepares a silica sol binder by mixing tetraethyl orthosilicate, a weak acid and water in a mass ratio of 1:0.02-0.06:6-12, and then immerses the SiC nanofiber membrane obtained in step (3) in a silica sol aqueous solution in a mass ratio of 1:50-100, and then performs lamination, directional freezing, drying and high-temperature curing to obtain a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel.

[0013] Furthermore, the spinning aid in step (1) is one or more of polyvinyl pyrrolidone, polyvinyl alcohol and polyethylene oxide;

[0014] Furthermore, the parameters of the electrospinning in step (1) are: voltage 20 kV to 22 kV, injection speed 1 mL / h to 1.2 mL / h, and the ambient temperature and humidity during electrospinning are 25±2° C. and 45±2%, respectively.

[0015] Furthermore, in the acidic aqueous solution of step (2), the acidic environment is provided by one or more of hydrochloric acid, nitric acid or sulfuric acid.

[0016] Furthermore, the reaction temperature and time of the hydrothermal reaction are respectively: 110°C to 130°C, 12h to 18h.

[0017] Furthermore, the reaction temperature and time in step (3) are respectively: 60°C to 90°C, 2h to 8h, and the reaction is repeated 6 to 10 times.

[0018] Furthermore, the weak acid in step (4) is provided by one or more of anhydrous oxalic acid, acetic acid or boric acid.

[0019] Furthermore, the number of stacked layers in step (4) is 5 to 10 layers.

[0020] Furthermore, in the silica sol aqueous solution, the content of silica sol is 0.5wt% to 3wt%.

[0021] Furthermore, the high-strength and low-thermal conductivity SiC-TiO2 nanofiber aerogel and its preparation method are characterized in that the high-temperature curing temperature is 800°C to 1000°C.

[0022] Because the present invention adopts the above technical means, it has the following beneficial effects:

[0023] The present invention proposes a multi-level structure synergistic enhancement strategy, which uses a hydrothermal method to in-situ grow a layer of TiO2 nanorod structure on the surface of SiC nanofibers, effectively improving the mechanical properties of aerogels. When the layered ceramic fiber aerogel is subjected to shear stress parallel to the fiber layer, the TiO2 nanorod structures grown on the surfaces of the arched cell structures close to each other cross each other, playing a role in fixing the fiber layer, thereby improving the overall mechanical stability. At the same time, by using high-temperature adhesive silica sol to form a stable bonding point at the fiber node, the mechanical properties of the aerogel are maximized.

[0024] In addition to improving the shear strength of ceramic aerogels, the TiO2 nanorod structure on the fiber surface can also act as an infrared shielding layer to reduce the radiative heat conduction of aerogels in high-temperature environments. TiO2 materials have high absorbance or reflectivity in the infrared radiation region, which can significantly reduce infrared transmittance, thereby reducing the thermal conductivity of aerogels in high-temperature extreme environments. Aerogels have excellent high elasticity, high shear resistance and thermal insulation properties, solving the problem of poor mechanical properties of traditional aerogels and high thermal conductivity in high-temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Shown is the preparation flow chart of strong and low thermal conductivity SiC-TiO2 nanofiber aerogel material. DETAILED DESCRIPTION

[0026] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.

[0027] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.

[0028] The present invention firstly prepares SiC nanofiber membrane by electrostatic spinning technology and high temperature pyrolysis process. Then, the SiC fiber membrane is immersed in TiO2 reaction solution, and after hydrothermal reaction and multiple immersions, a vertically arranged TiO2 nanorod layer is in situ grown on the fiber surface. Finally, the fiber membrane is stacked layer by layer in a silica sol aqueous solution, and high strength and low thermal conductivity SiC-TiO2 nanofiber aerogel is obtained by directional freezing, vacuum drying and high temperature calcination.

[0029] The present invention utilizes a multi-level synergistic enhancement strategy, adopts a hydrothermal method to in-situ grow a TiO2 nanorod structure on the surface of SiC fibers, stacks the fiber membranes layer by layer, and combines directional freeze casting technology to construct a ceramic nanofiber aerogel with a layered porous structure. TiO2 nanorods enhance the mechanical properties of the aerogel and reduce the heat conduction caused by infrared radiation in a high temperature environment through their cross-fixation and their own unique high infrared light reflection ability. The addition of silica sol as a high-temperature binder allows the fibers to form a stable bonding point, further improving the mechanical stability of the fiber network framework.

[0030] Specifically, the present invention provides a high-strength and low-thermal conductivity SiC-TiO2 nanofiber aerogel, which is composed of a multi-level layered SiC nanofiber membrane and a high-temperature binder. A TiO2 nanorod structure is in situ grown on the surface of the multi-level SiC fiber membrane. The TiO2 nanorod secondary structure can effectively improve the overall mechanical stability of the aerogel by enhancing the interlayer bonding force of the fiber membrane. At the same time, as a thermal infrared shielding material, the TiO2 nanorod structure can weaken the thermal radiation conduction of the aerogel in a high-temperature environment, thereby reducing the thermal conductivity of the aerogel at high temperatures. The added high-temperature binder forms a stable bonding point between the fibers, thereby giving the aerogel a higher mechanical strength.

[0031] The present invention provides a method for preparing a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel material, comprising the following steps:

[0032] Step (1) polycarbosilane, tetrahydrofuran, ethanol and a spinning aid are mixed and stirred to form a spinning solution, and then the spinning solution is subjected to an electrospinning process to form a precursor nanofiber membrane, and the fiber membrane is heat-treated to obtain a SiC nanofiber membrane.

[0033] Step (2) adding tetrabutyl titanate to an acidic aqueous solution and mixing and stirring to obtain a reaction solution A; immersing the above-mentioned SiC nanofiber membrane in the reaction solution A for hydrothermal reaction, washing, drying and calcining to obtain product A.

[0034] Step (3) melamine, nitric acid and hydrogen peroxide are mixed and stirred to prepare a reaction solution B; the product A described in step (2) is immersed in the reaction solution B, and then filtered and immersed, washed, dried and calcined repeatedly to finally obtain a SiC nanofiber membrane with a TiO2 nanorod layer uniformly grown on the fiber surface.

[0035] Step (4) is to mix and stir ethyl orthosilicate, weak acid and water to prepare a silica sol binder; the nanofiber membrane prepared in step (3) is immersed in a silica sol aqueous solution, and then laminated, directionally frozen, dried and high-temperature cured to obtain a ceramic fiber aerogel.

[0036] Preferably, the spinning aid is polyvinyl pyrrolidone; the mass ratio of polycarbosilane:tetrahydrofuran:ethanol:spinning aid is 2-3.5:10-18:2-8:0.5-0.8; the parameters of the electrospinning are: voltage 20kV-22kV, injection speed 1mL / h-1.2mL / h, and the ambient temperature and humidity during electrospinning are 25±2°C and 45±2%, respectively.

[0037] Preferably, the acidic aqueous solution and the acidic environment are provided by hydrochloric acid; the volume ratio of tetrabutyl titanate: acid source: water is 1:8-12:22-30; the reaction temperature and time of the hydrothermal reaction are respectively: 110°C-130°C, 12h-18h.

[0038] Preferably, the molar ratio of melamine, nitric acid and hydrogen peroxide is 0.01-0.05:0.5-0.8:50-60; the reaction temperature and time are 60°C-90°C, 2h-8h respectively; the reaction is repeated 6 to 10 times.

[0039] Preferably, the weak acid is provided by anhydrous oxalic acid; the mass ratio of tetraethyl orthosilicate: weak acid: water is 1:0.02~0.06:6~12; the mass ratio of the nanofiber membrane to the silica sol aqueous solution is 1:50~100; the number of stacked layers is 5~10 layers; the content of silica sol in the silica sol aqueous solution is 0.5wt%~3wt%; the high temperature curing temperature is 800℃~1000℃.

[0040] Example 1

[0041] Step 1: Add 2g of polycarbosilane to 17mL of a mixed solution of tetrahydrofuran: ethanol with a volume ratio of 12:5 and stir for 10min. After the polycarbosilane is completely dissolved, slowly add 0.6g of polyvinyl pyrrolidone while stirring, and stir at room temperature for 8h to obtain a spinning solution; then inject the spinning solution into a 20mL syringe for electrostatic spinning to obtain a flexible nanofiber precursor membrane; the electrospinning process parameters are: voltage 22KV, feed rate 1.2mL / h. Subsequently, the precursor fiber membrane is dried at 60°C for 3h under a vacuum environment, and placed in a muffle furnace at 200°C in an air atmosphere for curing for 2h. Finally, it is placed in a muffle furnace and calcined at 1100°C in an Ar atmosphere for 2h, and a SiC nanofiber membrane is obtained after natural cooling.

[0042] Step 2: Tetrabutyl titanate: hydrochloric acid: water are mixed in a volume ratio of 1:10:25 and stirred at room temperature for 2 hours. After stirring, the SiC fiber membrane is immersed in the reaction solution, and then the reactor is placed at 120°C for 16 hours. After cooling to room temperature, the fiber membrane is washed with deionized water, dried at 80°C, and finally calcined at 400°C in air atmosphere for 6 hours to obtain a SiC nanofiber membrane with a TiO2 seed layer coated on the fiber surface.

[0043] Step 3: Mix melamine, nitric acid and hydrogen peroxide in a molar ratio of 0.03:0.6:60, heat and stir at 80°C to obtain a reaction solution; then soak the fiber membrane described in step (2) in the reaction solution for 6 hours, vacuum filter and re-immerse, and repeat the operation 8 times; finally, wash with deionized water 3 times, dry and calcine at 600°C in an air atmosphere for 6 hours, and finally obtain a SiC nanofiber membrane with a TiO2 nanorod layer uniformly grown on the fiber surface.

[0044] Step 4: Mix 1g of tetraethyl orthosilicate, 0.05g of anhydrous oxalic acid and 8mL of water and stir for 8h to obtain a silica sol binder; then stack 6 layers of the fiber membrane obtained in step 3, immerse it in 50mL of a silica sol aqueous solution with a mass percentage concentration of 1wt%, and quickly freeze it with -196℃ liquid nitrogen, then place it in a freeze dryer and dry it for 72h to obtain an uncross-linked aerogel; finally, place the obtained aerogel in a muffle furnace and sinter it at 900℃ for 1h to obtain a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel sample 1.

[0045] Example 2

[0046] The difference between Example 2 and Example 1 is that the mass of polycarbosilane in the spinning solution in step 1 is changed from 2 g to 2.8 g, and the other steps are the same.

[0047] Example 3

[0048] The difference between Example 3 and Example 1 is that the volume ratio of tetrabutyl titanate: hydrochloric acid: water in step 2 is changed to 1:8:28, and the other steps are the same.

[0049] Example 4

[0050] The difference between Example 4 and Example 1 is that the molar ratio of melamine, nitric acid and hydrogen peroxide in step 3 is changed to 0.05:0.8:55, and the other steps are the same.

[0051] Example 5

[0052] The difference between Example 5 and Example 1 is that the immersion reaction time of the fiber membrane in the reaction solution in step 3 is changed from 6 hours to 10 hours, and the other steps are the same.

[0053] Example 6

[0054] The difference between Example 6 and Example 1 is that the content of silica sol binder in step 4 is changed from 1wt% to 2wt%, and the other steps are the same.

[0055] Table 1 Performance test results of high strength and low thermal conductivity SiC-TiO2 nanofiber aerogels of different embodiments

[0056]

[0057]

[0058] Table 2 Performance comparison results of other ceramic aerogels

[0059]

[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0061] As can be seen from Table 1, the high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel material obtained by the present invention has high strength, and its ultimate pressure is 110-140 kPa. And the high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel obtained by the present invention has excellent low thermal conductivity of 0.0688-0.0793 W / (m·K) (600°C) and a near-infrared light shielding performance of about 88%.

Claims

1. A high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel, characterized in that: The ceramic fiber aerogel is composed of a multi-level layered SiC nanofiber membrane and a silica sol binder, wherein a TiO2 nanorod structure is in-situ grown on the surface of the multi-level SiC fiber membrane, and the silica sol binder forms a stable bonding point between the fibers.

2. The method for preparing a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel according to claim 1, characterized in that: The following steps are involved: Step (1) polycarbosilane, tetrahydrofuran, ethanol and a spinning aid are mixed and stirred in a mass ratio of 2-3.5:10-18:2-8:0.5-0.8 to form a spinning solution, and then the spinning solution is subjected to an electrospinning process to form a precursor nanofiber membrane, and the fiber membrane is heat-treated to obtain a SiC nanofiber membrane; Step (2) adding tetrabutyl titanate to an acidic aqueous solution and mixing and stirring to obtain a reaction solution A, immersing the SiC nanofiber membrane in the reaction solution A for hydrothermal reaction, washing, drying and calcining to obtain a product A, wherein the volume ratio of tetrabutyl titanate: acid source: water is 1:8-12:22-30; Step (3) mixing melamine, nitric acid and hydrogen peroxide in a molar ratio of 0.01-0.05:0.5-0.8:50-60 to prepare a reaction solution B, soaking the product A in step (2) in the reaction solution B, and then repeatedly filtering and soaking, washing, drying and calcining to finally obtain a SiC nanofiber membrane with a TiO2 nanorod layer uniformly grown on the fiber surface; Step (4) prepares a silica sol binder by mixing tetraethyl orthosilicate, a weak acid and water in a mass ratio of 1:0.02-0.06:6-12, and then immerses the SiC nanofiber membrane obtained in step (3) in a silica sol aqueous solution in a mass ratio of 1:50-100, and then performs lamination, directional freezing, drying and high-temperature curing to obtain a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel.

3. The method for preparing a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel according to claim 2, characterized in that: The spinning aid in step (1) is one or more of polyvinyl pyrrolidone, polyvinyl alcohol and polyethylene oxide.

4. The method for preparing a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel according to claim 3, characterized in that: The parameters of the electrospinning in step (1) are: voltage 20 kV to 22 kV, injection speed 1 mL / h to 1.2 mL / h, and the ambient temperature and humidity during electrospinning are 25±2°C and 45±2%, respectively.

5. The method for preparing a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel according to claim 1, characterized in that: The acidic aqueous solution in step (2) has an acidic environment provided by one or more of hydrochloric acid, nitric acid or sulfuric acid.

6. The method for preparing a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel according to claim 4, characterized in that: The reaction temperature and time of the hydrothermal reaction are respectively: 110° C. to 130° C., 12 h to 18 h.

7. The method for preparing a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel according to claim 1, characterized in that: The reaction temperature and time in step (3) are respectively: 60°C to 90°C, 2h to 8h, and the reaction is repeated 6 to 10 times.

8. The method for preparing a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel according to claim 1, characterized in that: The weak acid in step (4) is provided by one or more of anhydrous oxalic acid, acetic acid or boric acid.

9. The method for preparing a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel according to claim 1, characterized in that: The number of stacked layers in step (4) is 5 to 10 layers.

10. The method for preparing a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel according to claim 1, characterized in that: In the silica sol aqueous solution, the content of silica sol is 0.5wt% to 3wt%.

11. The method for preparing a high-strength and low-thermal-conductivity SiC-TiO2 nanofiber aerogel according to claim 1, characterized in that: The high temperature curing temperature is 800°C to 1000°C.

Citation Information

Cited By

  • Ceramic nanofiber aerogel with high compression strength and low thermal conductivity and preparation method thereof

    CN121021173A

  • High-thermal-conductivity radiation refrigeration coating for 5G communication base station cabinet and preparation method of high-thermal-conductivity radiation refrigeration coating

    CN121045951A

  • Tubular aerogel composite material and preparation method thereof

    CN121537194A